Juvenile delinquency in a diverse society - Bates, Kristin A. (SAGE, 2024)
"Juvenile Delinquency in a Diverse Society, Fourth Edition", by Kristin A. Bates and Richelle S. Swan, takes a critical approach to juvenile delinquency. True stories and real-world examples allow readers to gain a critical understanding of juvenile delinquency, encouraging them to explore how theories of delinquency can be used to create new policies and programs in their own communities. -- From product description